Trolls world tour [videorecording (DVD)] - Aibel, Jonathan, 1969-; Berger, Glenn; Forbes, Maya; Wolodarsky, Wallace; Tippet, Elizabeth; Shapiro, Theodore, 1971- (Universal Pictures Home Entertainment, 2020)
Poppy and Branch discover that they are but one of six different Trolls tribes scattered over six different lands and devoted to six different kinds of music: Funk, Country, Techno, Classical, Pop and Rock. A member of hard-rock royalty, Queen Barb, aided by her father King Thrash, wants to destroy all other kinds of music to let rock reign supreme. With the fate of the world at stake, Poppy and Branch set out to visit all the other lands to unify the Trolls in harmony against Queen Barb.